Comparison of Corneal Biological Healing After Femtosecond LASIK and Small Incision Lenticule Extraction Procedure. (1st September 2016) - Xia, Lei; Zhang, Jing; Wu, Junshu; Yu, Keming
ABSTRACT: Purpose : To assess and compare the dry-eye-associated parameters and corneal biomechanical status after small-incision lenticule extraction (SMILE) and femtosecond laser-assisted in situ keratomileusis (FS-LASIK). Methods : Sixty-five patients' (128 eyes) were collected between November 2012 and April 2013. Thirty-five (69 eyes) underwent SMILE and thirty (59 eyes) underwent FS-LASIK. Visual acuity, manifest refraction, tear break-up time (TBUT), Schirmer's test (ST), corneal sensitivity, Ocular Surface Disease Index (OSDI), corneal hysteresis (CH) and corneal resistance factor (CRF) were evaluated preoperatively and 1 day, 1 week, 1 month, 3 and 6 months postoperatively. Results : There was no significant difference in visual outcomes of SMILE and FS-LASIK ( p = 0.208). TBUT, ST, CH and CRF decreased significantly after surgery in both groups (all p < 0.05); however, the decrease of TBUT, ST and CRF in the SMILE group was not as significant as that in the FS-LASIK group (all p < 0.05) and the change of CH value was comparable in both groups ( p = 0.052).Corneal sensitivity was significantly decreased in the FS-LASIK group postoperatively ( p < 0.05), but not significantly changed in the SMILE group ( p > 0.05). OSDI scores were significantly increased after surgery for the two groups (all p < 0.05), and the scores were much higher in the FS-LASIK group than in the SMILE group ( p = 0.000). Conclusion : The corneal biological healing of SMILE surgery was superior to FS-LASIK in the early period.